2010
DOI: 10.1093/cvr/cvq192
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial aldehyde dehydrogenase and cardiac diseases

Abstract: Numerous conditions promote oxidative stress, leading to the build-up of reactive aldehydes that cause cell damage and contribute to cardiac diseases. Aldehyde dehydrogenases (ALDHs) are important enzymes that eliminate toxic aldehydes by catalysing their oxidation to non-reactive acids. The review will discuss evidence indicating a role for a specific ALDH enzyme, the mitochondrial ALDH2, in combating oxidative stress by reducing the cellular ‘aldehydic load’. Epidemiological studies in humans carrying an ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(188 citation statements)
references
References 91 publications
4
174
0
10
Order By: Relevance
“…However, high oxidative stress, such as that occurring after I/R or in heart failure may trigger lipid peroxidation and accumulation of reactive aldehydes, namely 4-HNE and malondialdehyde (11,25). Aldehydes inactivate a number of macromolecules, including the proteasome, the electron transport chain in the mitochondria, as well as ALDH2 itself (12). Indeed, treatment with ALDH2 activator Alda-1 increased ALDH2 activity by two-fold and reduced infarct size by 60% in an in vivo model of myocardial infarction in rats (11).…”
Section: Mao-b Activity Through Ros and Aldehydes Contribute To Altermentioning
confidence: 99%
“…However, high oxidative stress, such as that occurring after I/R or in heart failure may trigger lipid peroxidation and accumulation of reactive aldehydes, namely 4-HNE and malondialdehyde (11,25). Aldehydes inactivate a number of macromolecules, including the proteasome, the electron transport chain in the mitochondria, as well as ALDH2 itself (12). Indeed, treatment with ALDH2 activator Alda-1 increased ALDH2 activity by two-fold and reduced infarct size by 60% in an in vivo model of myocardial infarction in rats (11).…”
Section: Mao-b Activity Through Ros and Aldehydes Contribute To Altermentioning
confidence: 99%
“…4-HNE is one of the most abundant aldehydes formed during oxidation of polyunsaturated fatty and oxidative stress, and it is capable of modifying key enzymes by forming protein adducts to inhibit protein function (12). A recent study demonstrated that mechanical dysfunction of cardiomyocytes induced by 4-HNE was ablated by ALDH2 (25).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Increasing evidence has revealed the beneficial role of ALDH2 against tissue and cellular injuries originated from alcohol, acetaldehyde and toxic aldehyde-induced reactive oxygen species formation (9-11). 4-HNE is a highly cytotoxic aldehyde that gets accumulated in the heart in response to ischemia/reperfusion insult, which in turn inactivates ALDH2 by protein adducts formation (12). Pharmacological enhancement of ALDH2 activity can protect the heart against ischemic injury (8).…”
Section: Introductionmentioning
confidence: 99%
“…), polyurethane, smog, cigarette smoke or motor vehicle exhaust. With their malodorous properties, some dietary and aromatic aldehydes are accepted as additives in food and cosmetics (e.g., citral, cinnamaldehyde, benzaldehyde, and retinal), though many others are cytotoxic (Chen, et al, 2010). Aldehydes could interact with thiol compounds of some proteins, leading to structural and functional alterations of these molecules (Weiner, et al, 2008).…”
Section: Aldehydesmentioning
confidence: 99%
“…Overconsumption of ethanol has been related to liver disease and several gastrointestinal and upper aerodigestive cancers. Numerous other cytotoxic and reactive aldehydes have been shown to be linked with other types of diseases (Hofseth & Wargovich, 2007, Perluigi, et al, 2009, Chen, et al, 2010.…”
Section: Aldehydesmentioning
confidence: 99%